O legado da saúde comunitária à produção do SUS: críticas à medicina de mercado e proposta de atenção primária na experiência de Braga, RS - Maia, Dyan Jamilles Brum (2022)
The study is part of a larger research, THE CONSTRUCTION OF THE SUS IN MUNICIPALITIES IN THE INTERIOR OF RS: INVENTORY OF EXPERIENCES IN HEALTH PROMOTION AND PRIMARY CARE, registered on the UFSM Project Portal under number 055865. It is an effort by three institutions: UFSM, Unijuí and UFRGS, which seeks to highlight community health experiences that took place in the 1980s, in the Alto Uruguay region. This research report constitutes a master's thesis on one of the experiences investigated: community health in the city of Braga/RS. The main objective is to understand the community health experience in the city of Braga/RS. This is a case study. The investigation techniques were individual and open interviews and focus groups. The research was approved by the CEP. The study listed two categories: criticism of market medicine and Primary Health Care (PHC); Highlighting, in the APS category, community participation and intersectorality. Braga's community health experience results from the action of social movements in the region of Ijuí, RS, especially the nursing course at the Foundation for Integration and Development of RS (Fidene), currently the Regional University of the Northwest of Rio Grande do Sul (Unijuí) and is part of the fight for the right to health and, therefore, in the Brazilian health reform movement. It seeks to overcome market medicine through community participation and development of primary care. The project is related to international movements, especially the Economic Commission for Latin America and the Caribbean (ECLAC). Intersectorality is a characteristic of the experience, most evident in the Pedro Garcia project. The investigation allowed recording the experience and highlighting its contributions to the health reform movement and to the development of primary care and defense of the Unified Health System (SUS).